2011
DOI: 10.1007/s10753-011-9319-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Modulates the Inflammatory Response in Ifosfamide-Induced Hemorrhagic Cystitis

Abstract: We investigated whether interleukin-4 (IL-4) is present and capable of reducing inflammatory changes seen in ifosfamide-induced hemorrhagic cystitis. Male Swiss mice were treated with saline or ifosfamide alone or ifosfamide with the classical protocol with mesna and analyzed by changes in bladder wet weight (BWW), macroscopic and microscopic parameters, exudate, and hemoglobin quantification. In other groups, IL-4 was administered intraperitoneally 1 h before ifosfamide. In other experimental groups, C57BL/6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Additionally, IL-4 and IL-10 could down-regulate the formation of NO by blocking the NF-kB activation pathway [43] and inhibiting the expression of iNOS [44], respectively, which could partially explain the negative effect of LPC20:4 and LPC22:6 on LPC16:0-induced NO formation. Furthermore, the decrease in LPC16:0-induced PGE 2 formation level might be partly from the inhibitory effect of IL-4 and IL-10 on COX-2 enzyme as reported previously [45][46][47][48]. Taken together, it was suggested that elevation of IL-4 and IL-10 levels also contributed to the anti-inflammatory action of LPC20:4 and LPC22:6 in LPC16:0-induced inflammation.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, IL-4 and IL-10 could down-regulate the formation of NO by blocking the NF-kB activation pathway [43] and inhibiting the expression of iNOS [44], respectively, which could partially explain the negative effect of LPC20:4 and LPC22:6 on LPC16:0-induced NO formation. Furthermore, the decrease in LPC16:0-induced PGE 2 formation level might be partly from the inhibitory effect of IL-4 and IL-10 on COX-2 enzyme as reported previously [45][46][47][48]. Taken together, it was suggested that elevation of IL-4 and IL-10 levels also contributed to the anti-inflammatory action of LPC20:4 and LPC22:6 in LPC16:0-induced inflammation.…”
Section: Discussionsupporting
confidence: 70%
“…interleukin-1 beta (IL-1 ), and the inducible isoform of nitric oxide synthase (iNOS) in ileal loop tissue sections were done using a previously described streptavidine-biotinperoxidase method [35][36][37]. In this regard, TNF-and IL-1 are pro-inflammatory …”
Section: Detection Of Tnf- Il-1 and Inos By Immunohistochemistrymentioning
confidence: 99%
“…IPSE also features a nuclear localization sequence (NLS) which facilitates its entry into host cell nuclei and subsequent modulation of transcription [4,5]. Macedo et al have reported that administration of IL-4 to mice with ifosfamide-induced hemorrhagic cystitis alleviates bladder injury [6]. This led us to test IPSE in this model.…”
Section: Introductionmentioning
confidence: 99%